2007
DOI: 10.3748/wjg.v13.i21.2932
|View full text |Cite
|
Sign up to set email alerts
|

Leptin treatment ameliorates acute lung injury in rats with cerulein-induced acute pancreatitis

Abstract: Exogenous leptin attenuates inflamma-tory changes, and reduces pro-inflammatory cytokines, nitric oxide levels, and CD40 expression in cerulein-induced AP and may be protective in AP associated ALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…In these studies, extreme weight loss or gain has been associated with the development of emphysema and asthma, respectively. Further experimental studies have shown that leptin, a molecule derived from adipocytes, regulates surfactant production in type II pneumocytes and protects the lung from acute injury (2,14).…”
mentioning
confidence: 99%
“…In these studies, extreme weight loss or gain has been associated with the development of emphysema and asthma, respectively. Further experimental studies have shown that leptin, a molecule derived from adipocytes, regulates surfactant production in type II pneumocytes and protects the lung from acute injury (2,14).…”
mentioning
confidence: 99%
“…In patients with AP, a correlation between serum leptin and disease severity has been reported by some investigators but not by others (11,12). Although in animal models administration of leptin decreases AP severity (13)(14)(15)(16), more severe disease is present in leptin-deficient ob/ob and leptin receptordeficient db/db mice as well as leptin-receptor mutant fa/fa rats (17,18). However, the differential effect of obesity versus leptin deficiency has not been fully investigated.…”
mentioning
confidence: 99%
“…TNF-α and IL-1β are also released from activated neutrophils following stimulation. [29,30] In our study, the TNF-α and IL-1β levels were lower in the ALA-treated pancreatitis group than the saline-treated group (p<0.01). These results suggest that ALA decreases the inflammatory response by inhibiting activation and infiltration of neutrophils, which play a role in triggering tissue damage, and that ALA protects the pancreas tissue from free oxygen radical-induced damage.…”
Section: Histologic Preparation and Analysismentioning
confidence: 45%